Altered electrophysiology mechanism related to inhibitory control in adults with insomnia - Ding, Xiaobin; He, Liang; Geng, Xicong; Zhao, Xuan; He, Zijing; Zhang, Xiangzi (Frontiers in Neurology, 2023)
Background Insomnia disorder (ID), one of the most common psychophysiological disorders, can cause a serious burden on the individual's work and academic performance. Cognitive dysfunction often exists in patients with insomnia, which negatively affects their living quality. Inhibitory control (IC), as a vital cognitive function, allows individuals to suppress attention, behavior, or thoughts that are irrelevant to the task, so as to effectively adapt to the current goal. The earlier studies on the inhibitory control of insomnia patients predominantly used subjective scales for evaluation and that can have drawbacks because they don't provide an objective assessment. Methods In order to investigate the inhibitory control function of insomniacs, this research subdivides inhibitory control into response inhibition and conflict inhibition. The response inhibition and conflict inhibition capacities of insomniacs were evaluated using the two-choice oddball task and the color-word stroop task, and accordingly the association between insomnia disorder and inhibitory control capacity as well as its cognitive neural mechanism was able to be examined. Results Behavioral results finding, insomniacs conducted the two-choice oddball test and the color-word stroop task with lower accuracy and slower reaction times when compared to healthy sleepers. ERP results finding, when performing the two-choice oddball task, the P3 amplitude of the insomniacs was significantly lower than that of healthy sleepers while there was no significant difference between the two groups' N2 amplitudes. At the same time, when completing the color-word stroop task, the insomniacs' N450 amplitude was significantly lower than that of healthy sleepers. Discussion The above findings suggest that in response inhibition tasks, insomniacs may have weaker motor inhibition abilities, and similarly perform weaker conflict monitoring abilities in conflict inhibition tasks, which indicates that insomniacs' inhibitory control is impaired compared to that of healthy sleepers. This study thus relates to the finding at the electrophysiological level that there is a certain correlation between insomnia and a decline in inhibitory control ability, which may suggest that improving inhibitory control function in patients with insomnia is a clinically significant and worthwhile area of adjuvant treatment.